B09 Biological motion detection – a cognitive test for pigs transgenic for the huntington gene?. (September 2018) - Matheis, Tamara; Schubert, Robin; Rieke, Lorena; Schuldenzucker, Verena; Motlik, Jan; Fels, Michaela; Kemper, Nicole; Muratori, Lisa; Reilmann, Ralf
Abstract : Backround: The ability to detect biological motion (BM) by observing point-light displays is well known in healthy individuals. A recent study in Huntington's disease demonstrated a decline in the ability to detect and interpret BM for humans. Different studies verified the ability to detect biological motion by using point-light displays in animals as well. To establish the easy and non-invasive biological motion detection test in preclinical research we want proof the ability of Libechov Minipigs to perceive BM and differentiate between BM and random movement. Objective: The aim of this study is to investigate whether perception of BM in pigs could serve as an early and non-invasive marker for onset and progression of a Huntington phenotype in transgenic pigs. Moreover the Biological Motion test could be a further step to investigate new therapeutic approaches in a preclinical large animal model. Methods: To verify the perception of BM in minipigs we filmed the trot of a healthy pig and used this video to create a point-light pig consisting of 16 withe points moving on a black background. A new semi-automated setup is used to display the pig BM in comparison to 16 random moving dots. 13 Libechov Minipigs (5 transgenic and 8 wildtyp) participate in the study. Conclusion: Data collection and analysis is ongoing. The new setup enables an automated data collection. First results about the feasibility and information provided by this assessment will be presented to guide further investigations about motion detection capabilities in minipigs. Acknowledgement: This study was funded by the CHDI foundation.